Komizm rymów w utworach Andrzeja Waligórskiego. Uwagi wstępne - Korpysz, Tomasz (Colloquia Litteraria, 2024)
In the rich literature of humorology, comism induced by the juxtaposition of specially selected words or word combinations in rhyming pairs is very rarely subjected to scientific reflection, although it is relatively oſten used in various types of texts (especially satirical, but also children’s texts or songs). Andrzej Waligorski used this comic mechanism very oſten in his works. In his analyzed poems, broken rhyme (also called broken and divided rhyme), broken-folded rhyme, homonymous rhyme and repeated rhyme do not occur. On the other hand, on several occasions the author used composed rhyme (e.g.: szyja – ci ja, w pierś się – Engelsie) and allusive rhyme, but most oſten he created made up rhymes (e.g.: stolicą – bógwico, plon – maison, kiśli – wymyślił) and stylistic rhymes (wszędy – urzędy, komnacie – gacie, dezynwolturą – kurą, dyrektywy – lewatywy, chabrze – ubabrze, ino – Portofino). The latter, in particular, both from the recipient and the sender require knowledge of a rich vocabulary from a variety of semantic and stylistic fields, as well as developed linguistic competence, including humorous competence. The fragments of works cited in the article undoubtedly prove the true satirical artistry of their author.